ANALYSIS OF Tanacetum Vulgare L. INTRODUCTION IN THE CONDITIONS OF THE POLISSYA OF UKRAINE - Svitelskyi, Mykola; Romaniuk, A.; Maksymova, T.; Nasinnyk, I. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article presents the results of studies on the study of ecological and biological features of Tanacetum vulgare L. under conditions of a botanical nursery of the Zhytomyr National Agroecological University. As a result of studying the biology of flowering and pollination of ordinary flavor, it has been established that the main method of pollination is cross-sectional. A slight binding of seeds due to selfpollination within a single basket is allowed. Methodological approaches to breeding work with this crop should be similar for cross-pollinated plants. The study of the biological characteristics of tansy ordinary allowed to establish the expediency of its cultivation in Zhytomyr region as a multi-cultural and recommend the main evaluation of breeding material in plants of the second year of life. In the selection work, in the initial stages of the scheme, it is necessary to use the seedling method of cultivation, which allows one year after the birth of the seed collection of the best collection samples and, thus, contribute to accelerating the selection process. The population phenotypic variability of quantitative characteristics is determined within the population. In the course of research, a relatively high correlation was found between raw material yields on the one hand; the number of generative shoots, the number and weight of baskets in the inflorescence – on the other (r = 0.76, 0.74, 0.73, respectively). Significant, and less pronounced correlation is observed between the yield of raw materials and seeds (r = 0.53). The maintenance of the amount of flavonoids in the first year of vegetation significantly correlates with its mass fraction in the second year of life (r = 0.75), which indicates the effectiveness of selection on this basis in the first year of vegetation. Detected correlations are the basis for predicting the selection of valuable forms on indicator basis, as well as for simplification of selection. Collection and study of Tanacetum vulgare L. collection of 105 samples of different geographical origin. 25 best populations are distinguished which are characterized by high indicators of individual characteristics – yield of inflorescences, seeds, contents of the sum of flavonoids and phenolcarboxylic acids and have value as valuable source material for selection of tansy by different methods. According to a set of economically useful features, selected collectible samples: 972-02 (Germany), 992-01 (Slovakia), 733-01 (Poland), which exceed the control of raw material yield by 12-34%, and the content of active substances at 13-27%, which areincluded in the breeding process for a comparative trial at the finalstages of the breeding scheme. The method of vegetative reproductionof Tanacetum vulgare L. by cloning rhizomes is developed, which helpsto preserve and fix the economic value signs of the allocated numbers, simplify and accelerate the breeding work for the creation of high-yielding varieties that meet the requirements of production.